Upaya Meningkatkan Sikap Saling Menghargai Pada Anak Usia 5-6 Tahun Melalui Metode Bermain Peran - Nabila Azrina; Abdul Aziz Rusman (Universitas Muhammadiyah Metro, 2026)
This research aims to increase mutual respect among children at Raudhatul Athfal (RA) AZRINA aged 5 to 6 years through role-playing techniques. The background of this research is children's weak social-emotional skills, which are indicated by their inability to collaborate, respect peers, use polite language, and regulate their emotions in social situations. This research uses the Kemmis and McTaggart model of Classroom Action Research (PTK), which consists of two cycles of planning, action implementation, observation and reflection. A total of 20 children in group B, 8 boys and 12 girls, were research subjects. The observation sheet about mutual respect functions as the main tool. Obtaining research data is achieved through the application of several techniques, namely observation, interviews and searching for documents relevant to the research focus. Role-playing exercises, which give children the opportunity to connect, cooperate, communicate and understand the emotions of others in scenarios similar to real life, are used to carry out the action. The average percentage of achievement increased from 39% in pre-cycle to 58% in Cycle I and 91.2% in Cycle II, indicating increased mutual respect, according to research findings. These results indicate that children at RA AZRINA aged 5 to 6 years benefit from a role-playing approach in developing mutual respect.